2019
DOI: 10.1021/acsami.8b19973
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Formation Mechanism of Solid–Liquid Electrolyte Interphases on LiPON Thin Films

Abstract: Most commercial lithium-ion batteries and other types of batteries rely on liquid electrolytes, which are preferred because of their high ionic conductivity, and facilitate fast charge-transfer kinetics at the electrodes. On the other hand, hybrid battery concepts that combine solid and liquid electrolytes might be needed to suppress unwanted shuttle effects in liquid electrolyte-only systems, in particular if mobile redox systems are involved in the cell chemistry. However, at the then newly introduced interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Thereby, SLEI thickness of about 25 nm was observed after 24 h. The SLEI formation mechanism on "LiPON" was found to involve the quick deposition of a mostly covering interphase with some pinholes left, which are subsequently slowly filled, explaining the increase in the interphase resistance. In these experiments, a two-layer SLEI was observed, with one layer being attributed to inorganic lithium salts and the other to a presumably polymeric material [50].…”
Section: Solid/liquid Interfacesmentioning
confidence: 79%
See 2 more Smart Citations
“…Thereby, SLEI thickness of about 25 nm was observed after 24 h. The SLEI formation mechanism on "LiPON" was found to involve the quick deposition of a mostly covering interphase with some pinholes left, which are subsequently slowly filled, explaining the increase in the interphase resistance. In these experiments, a two-layer SLEI was observed, with one layer being attributed to inorganic lithium salts and the other to a presumably polymeric material [50].…”
Section: Solid/liquid Interfacesmentioning
confidence: 79%
“…The interphase formation on "LiPON" thin films immersed in ether-based LEs was investigated using neutron reflectometry (NR), quartz crystal microbalance (QCM) and atomic force microscopy (AFM) measurements [50]. Thereby, SLEI thickness of about 25 nm was observed after 24 h. The SLEI formation mechanism on "LiPON" was found to involve the quick deposition of a mostly covering interphase with some pinholes left, which are subsequently slowly filled, explaining the increase in the interphase resistance.…”
Section: Solid/liquid Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports of LiPON suggested that the material was stable in contact with metallic Li over a stability window of 5.5 ± 0.2 V (Yu et al, 1997); however this has been questioned in subsequent studies. The propensity of LiPON to decompose when in contact with a number of different materials has been investigated, including metallic lithium (Motoyama et al, 2015(Motoyama et al, , 2018Sicolo et al, 2017;Westover et al, 2019), the ubiquitous LiCoO 2 cathode (Li et al, 2014;Schwöbel et al, 2015;Sicolo and Albe, 2016;Wang et al, 2016;Fingerle et al, 2017;Weiss et al, 2019), and the nickel manganese spinel (West et al, 2016;Thai and Lee, 2017;Lv et al, 2020). While one of LiPONs strengths as an electrolyte appears to be its resistance to lithium penetration (Westover et al, 2019), there are a number of interfacial reactions which yield gaseous evolution (Put et al, 2018) and resistive interfacial layers 2018with permission from the Royal Society of Chemistry.…”
Section: Stability Of Liponmentioning
confidence: 99%
“…While one of LiPONs strengths as an electrolyte appears to be its resistance to lithium penetration (Westover et al, 2019), there are a number of interfacial reactions which yield gaseous evolution (Put et al, 2018) and resistive interfacial layers 2018with permission from the Royal Society of Chemistry. (Li et al, 2014;Hausbrand et al, 2015;Weiss et al, 2019) at both the anode and cathode interfaces which may limit the future application of LiPON SSEs.…”
Section: Stability Of Liponmentioning
confidence: 99%